Marketing Mix, Brand Equity, and Purchase Decisions of Packaged Rice Products - Mochammad Reza Firmansyah; Ujang Sumarwan; Muhammad Mukti Ali (Jurnal Manajemen & Agribisnis, 2021)
In selling packaged rice products, Perum BULOG needs to implement the right marketing strategy in order to increase the buying interest of prospective consumers. This study aims to analyze factors that affect brand equity and purchasing decisions of packaged rice products. The research design uses a descriptive approach through surveys by disseminating questionnaires online. The research was conducted in September-October 2020 on 270 rice consumers in DKI Jakarta and Bodetabek who were selected using non-probability sampling method through convenience sampling technique. The variables studied in this study were product, price, place, promotion, brand equity, and purchasing decisions. Data analysis method using SEM analysis with Lisrel 8.80 software. The results showed that product, price, place, and promotion had a significant positive influence on brand equity and purchasing decisions. The variables that most influence purchasing decisions are product, place, and brand equity. Based on the results of the study, it can be concluded that product, place, and brand equity are factors that should be a top priority for manufacturers to make improvements and development. In addition, rice products sold using brands and packaging are more attractive to consumers than rice products sold without brands and packaging. In this regard, in addition to the marketing mix strategy, manufacturers must implement brand and packaging strategies well to improve consumer purchasing decisions on their rice products. Keywords: brand equity, marketing mix, packaged rice products, purchase decisions, SEM